Foundations of health information management / Nadinia A Davis - Davis, Nadinia A.
Foundations of Health Information Management, 5th Edition is an absolute must for any student beginning a career in HIM. By focusing on healthcare delivery systems, electronic health records, and the processing, maintenance, and analysis of health information, this engaging, easy-to-understand text presents a realistic and practical view of technology and trends in healthcare. It readies you for the role of a Registered Health Information Technician, who not only maintains and secures accurate health documentation, but serves as a healthcare analyst who translates data into useful, quality information that can control costs and further research. The fifth edition follows the CAHIIM 2018 HIM Associate Degree curriculum competencies, preparing you for the RHIT credentialing exam. EHR samples, practice exercises, and new Bloom’s-level Competency Milestone features help ensure mastery of all competencies.